Morphology‐Dependent Bioadhesion and Bioelimination of Hyaluronan Particles Administered in the Bladder. Issue 5 (3rd May 2022) - Diaz-Salmeron, Raul; Toussaint, Balthazar; Cailleau, Catherine; Ponchel, Gilles; Bouchemal, Kawthar
Abstract : Bioadhesion In article number 2100138, Kawthar Bouchemal and co‐workers demonstrate that the flat morphology of hyaluronan particles significantly improves bioadhesion and decreases bioelimination from the bladder. Bioadhesion kinetics are evaluated ex vivo on rat bladder mucosa, while particle bioelimination is studied in vivo using a real‐time imager system. This investigation could open opportunities for efficient drug delivery.